Konsumsi Inhibitor dan Enhancer Zat Besi Kaitannya Dengan Status Anemia Pada Siswi SMAN 6 Denpasar - Monika, Ni Ketut Rosa; Eka Padmiari, Ida Ayu; Ambartana, I Wayan (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Anemia is a condition in which there is a total shortage of red blood cells or hemoglobin levels less than normal or decreased levels of red blood cells/hemoglobin in the blood so that the body's physiological needs are not fulfilled (Nabilla dkk., 2022). This study aims to determine the consumption of iron inhibitors and enhancers in relation to anemia status in female students of SMAN 6 Denpasar Selatan. The type of research used was observational with a cross sectional design. The research sample was 62 class XI students at SMAN 6 South Denpasar. Data collection was carried out by taking hemoglobin levels in female female students and interviews using the SQ FFQ questionnaire on the consumption of iron inhibitors and enhancers. The data collected included data on anemia status, consumption of inhibitors and consumption of iron enhancers in female adolescents. To determine the relationship between anemia status and consumption of iron inhibitors and enhancers. Pearson's correlation analysis was carried out. Anemia categories are divided into 2, namely not anemia (≥12 g/dL) and anemia (12 g/dL). Based on the research, out of 62 samples, there were 48 female students who were not anemic and 14 female students who were anemic.  The lowest hemoglobin level was 9.1 g/dL, the highest was 17.8 g/dL, the average was 15 g/dL. Consumption of tea (96.7%) and spinach (100.0%), and consumption of oranges (100.0%) and chicken meat (100.0%) in the last 1 month. The results showed that there was a relationship between consumption of iron inhibitors and anemia status in young women (p-value = 0.034). For the analysis test results of consumption of iron enhancers with anemia status in young women showed a relationship (p-value = 0.000).